Processed water-column current velocity and acoustic reflectivity data from a mining trial at the Belgian (GSR) contract area in the Clarion Clipperton Zone during the MANGAN 2021 expedition - Gazis, Iason-Zois; Diaz, Mélanie; Mohrmann, Jochen; Heger, Karl; de Stigter, Henko; Haeckel, Matthias; Greinert, Jens (PANGAEA, 2025)
The data were acquired with 13 ADCP sensors mounted on 12 seafloor platforms at successive distances (50 m to 1800 m) from the collector impact site in the Belgian (GSR) contract area in the Clarion Clipperton Zone (CCZ). The sensors used are Teledyne RDI Workhorse Sentinel ADCP at 300kHz, Teledyne RDI Workhorse Sentinel ADCP at 1.2 MHz and Nortek ADCP at 2 MHz. The data processing is described in Gazis et al. 2025. The data format is compatible with Digital Earth Viewer (https://digitalearthviewer-glodap.geomar.de/ )
Keywords: ADCP; CCZ; current velocity; Mining